Problematika Geng Motor di Kabupaten Kuningan dalam Prespektif Sosiologi Hukum - Diding Rahmat (UNIFIKASI : Jurnal Ilmu Hukum, 2014)
Brutality motorcycle gang is due to the social phenomenon of metamorphosis and development of information technology then is not filtered and not accommodated komferhensip about how pencegahanya action , it is the analysis that the majority of gang members are children that have motors and often commit crimes and violate social norms there . As a result of the brutal and unlawful actions that ultimately the future of motorcycle gang members tend to be aged under child protection laws they are still called the future of their children because they have to face a bleak life in bars and deprived of their freedom of expression , it is different with children outside bars detainees who have the freedom to express and execute education as befits a normal child his age . Factors behind them consists of internal factors and external factors , internal factors such as for some is not healthy mental attitude of a motorcycle gang members , disharmony in the family , an outlet disappointment , the economy needs a boost , aberrant learning process , lack of attention and affection as well as low levels of education among them while external factors , namely the need for law enforcement officers to always take preventive actions in handling cases motorcycle gangs and local community participation in order to swiftly carry out preventive.measures.as.well. Keywords: Problems , Gank , Motorcycle , Sociological